Analysis of tooth mark patterns on bone remains caused by wolves (Canis lupus) and domestic dogs (Canis lupus familiaris) for taxonomic identification: A scoping review focused on their value as a forensic tool. - Toledo González, Victor Antonio; Ortega Ojeda, Fernando Ernesto; Fonseca Platini, Gabriel; García Ruiz, Carmen; Pérez Lloret, Pilar (Applied Animal Behaviour Science, 2021)
The interaction between canids and humans is not free of conflicts. In Europe, wolves and dogs' attacks on domestic animals cause social and financial damages. The governments spend significant sums in compensation payments. Some of the allegations of wolf attacks on livestock may be false or difficult to prove. The insufficient expertise and unreliable methods used during the investigations often make it difficult to achieve a successful perpetrator identification, which leads to the stigmatization of this species and wrong paid compensations. Comparative studies of wolf and dog bite marks and tooth marks, to identify a potential aggressor agent, are very limited. In our study, 12,120 records were reviewed and only 16 of them fulfilled the search criteria set by the authors. Only one article carried out, exclusively, a comparison of wolf and dog bite mark patterns. These studies are commonly used in archaeological, paleontological and taphonomic contexts, but not in forensics. Despite the notable advances in bite mark analysis, most studies were carried out comparing bite marks from wolves and/or dogs and taxa belonging to other families. Currently, in forensic context, there is inconclusive evidence to certainly distinguish if the cause of death was created by wolves or domestic dogs using the forensic analysis of tooth/bite marks patterns from both canids (beyond any reasonable doubt). New and complementary forensic tools must be developed to differentiate between these two subspecies with a higher degree of certainty. Forensic veterinary odontology could play an important role in fulfilling this goal. The aim of the present work is to review and evaluate the studies on the identification of tooth marks on bone remains caused by two subspecies belonging to the same genus, wolves and domestic dogs.